The effect of change in flowrate on power spectral density (PSD) of automotive radiator system for flow-induced vibration monitoring - M. S. M., Sani; Azmi, W. H.; N. F. D., Razak; Zhang, B. (IOP Publishing, 2019)
The dynamic motion of internal fluid flow caused an interaction between the fluid's dynamic forces and a structure’s inner wall. This phenomenon will induce unstable vibration into the system and recently called flow-induced vibration. In this study, an experimental analysis was performed to identify the changes in the characteristics of vibration measured on an automotive radiator resulting from internal flow in a circular heated tube. The vibration result is presented in terms of Power Spectral Density (PSD) that shows the strength of the energy variations as a function of frequency. Water was used as the working fluid operate with engine temperature range from 80 to 90 ℃. The air flow velocities of radiator cooling fan were varied from 1.0 to 1.9 m/s and the water flowrates were 2.2, 2.8, 3.2 and 3.8 l/min. Experimental results are presented and indicated that PSD values are dependant to the fluid flowrate. It is also analysed that relationship between vibrations (PSD) and flowrate is influenced by the change of radiator cooling fan speed. Apart from that, the paper also develops a set of vibration features that will assist in identifying low flow conditions in automotive radiator. 1